Simultaneous management of disordered phosphate and iron homeostasis to correct fibroblast growth factor 23 and associated outcomes in chronic kidney disease. Issue 4 (July 2020) - Courbon, Guillaume; Martinez-Calle, Marta; David, Valentin
Abstract : Purpose of review: Hyperphosphatemia, iron deficiency, and anemia are powerful stimuli of fibroblast growth factor 23 (FGF23) production and are highly prevalent complications of chronic kidney disease (CKD). In this manuscript, we put in perspective the newest insights on FGF23 regulation by iron and phosphate and their effects on CKD progression and associated outcomes. We especially focus on new studies aiming to reduce FGF23 levels, and we present new data that suggest major benefits of combined corrections of iron, phosphate, and FGF23 in CKD. Recent findings: New studies show that simultaneously correcting iron deficiency and hyperphosphatemia in CKD reduces the magnitude of FGF23 increase. Promising therapies using iron-based phosphate binders in CKD might mitigate cardiac and renal injury and improve survival. Summary: New strategies to lower FGF23 have emerged, and we discuss their benefits and risks in the context of CKD. Novel clinical and preclinical studies highlight the effects of phosphate restriction and iron repletion on FGF23 regulation.